Fully guided and phase locked Ti:PPLN waveguide squeezing for applications in quantum sensing - Domeneguetti, Renato; Stefszky, Michael; Herrmann, Harald; Silberhorn, Christine; Andersen, Ulrik L.; Neergaard-Nielsen, Jonas S.; Gehring, Tobias (Optics Letters)
This work reports a fully guided setup for single-mode squeezing on integrated titanium-indiffused periodically poled nonlinear resonators. A continuous-wave laser beam is delivered and the squeezed field is collected by single-mode fibers; up to −3.17(9) dB of useful squeezing is available in fibers. To showcase the usefulness of such a fiber-coupled device, we applied the generated squeezed light in a fiber-based phase sensing experiment, showing a quantum enhancement in the signal-to-noise ratio of 0.35 dB. Moreover, our investigation of the effect of photorefraction on the cavity resonance condition suggests that it causes system instabilities at high powers.
Keywords: Atomic and Molecular Physics; and Optics

Numerical analysis of the coherent mechanism producing negative polarization at backscattering from systems of absorbing particles - Alhaddad, Samer; Grynko, Yevgen; Farheen, Henna; Förstner, Jens (Optics Letters)
We study a double-scattering coherent mechanism of negative polarization (NP) near opposition that is observed for powder-like surfaces. The problem is solved numerically for absorbing structures with irregular constituents, cubes, spheres, and ellipsoids larger than the wavelength of incident light. Our simulations show that double scattering between two random irregular particles shows weak NP. Adding one more particle significantly increases the relative contribution of double scattering which enhances NP. Simulations with regular shapes and controlled geometric parameters show that the interference mechanism is sensitive to the geometry of the scattering system and can also result in no polarization or even strong enhancement of positive polarization at backscattering.
Keywords: tet_topic_scattering

Asymmetric, non-uniform 3-dB directional coupler with 300-nm bandwidth and a small footprint - Nikbakht, Hamed; Khoshmehr, Mohammad Talebi; van Someren, Bob; Teichrib, Dieter; Hammer, Manfred; Förstner, Jens; Akca, B. Imran (Optics Letters)
Here we demonstrate a new, to the best of our knowledge, type of 3-dB coupler that has an ultra-broadband operational range from 1300 to 1600 nm with low fabrication sensitivity. The overall device size is 800 µm including in/out S-bend waveguides. The coupler is an asymmetric non-uniform directional coupler that consists of two tapered waveguides. One of the coupler arms is shifted by 100 µm in the propagation direction, which results in a more wavelength-insensitive 3-dB response compared to a standard (not shifted) coupler. Moreover, compared to a long adiabatic coupler, we achieved a similar wavelength response at a 16-times-smaller device length. The couplers were fabricated using the silicon nitride platform of Lionix International. We also experimentally demonstrated an optical switch that is made by using two of these couplers in a Mach–Zehnder interferometer configuration. According to experimental results, this optical switch exhibits –10 dB of extinction ratio over the 1500–1600 nm wavelength range. Our results indicate that this new type of coupler holds great promise for various applications, including optical imaging, telecommunications, and reconfigurable photonic processors where compact, fabrication-tolerant, and wavelength-insensitive couplers are essential.
Keywords: tet_topic_waveguide

Unidirectional vortex waveguides and multistable vortex pairs in polariton condensates - Gao, Xinghui; Hu, Wei; Schumacher, Stefan; Ma, Xuekai (Optics Letters)
Keywords: Atomic and Molecular Physics; and Optics

Multistable circular currents of polariton condensates trapped in ring potentials - Barkhausen, Franziska; Schumacher, Stefan; Ma, Xuekai (Optics Letters)
Keywords: pc2-ressources

Topological edge states of nonequilibrium polaritons in hollow honeycomb arrays. - Ma, Xuekai; Kartashov, YV; Ferrando, A; Schumacher, Stefan (Optics Letters)

Multistable circular currents of polariton condensates trapped in ring potentials. - Barkhausen, F; Schumacher, Stefan; Ma, Xuekai (Optics Letters)

Chiral condensates in a polariton hexagonal ring. - Ma, Xuekai; Kartashov, YV; Kavokin, A; Schumacher, Stefan (Optics Letters)

General framework for the analysis of imperfections in nonlinear systems - Santandrea, Matteo; Stefszky, Michael; Silberhorn, Christine (Optics Letters)

Bloch oscillations of multidimensional dark soliton wave packets and light bullets - Driben, R; Ma, Xuekai; Schumacher, Stefan; Meier, Torsten (Optics Letters)

Intensity surge and negative polarization of light from compact irregular particles - Grynko, Yevgen; Shkuratov, Yuriy; Förstner, Jens (Optics Letters)
We study the dependence of the intensity and linear polarization of light scattered by isolated particles with the compact irregular shape on their size using the discontinuous Galerkin time domain numerical method. The size parameter of particles varies in the range of X = 10 to 150, and the complex refractive index is m = 1.5 + 0i. Our results show that the backscattering negative polarization branch weakens monotonously, but does not disappear at large sizes, up to the geometrical optics regime, and can be simulated without accounting for wave effects. The intensity backscattering surge becomes narrower with increasing particle size. For X = 150, the surge width is several degrees.
Keywords: tet_topic_scattering

Light scattering by irregular particles much larger than the wavelength with wavelength-scale surface roughness - Grynko, Yevgen; Shkuratov, Yuriy; Förstner, Jens (Optics Letters)
We simulate light scattering by random irregular particles that have dimensions much larger than the wavelength of incident light at the size parameter of 𝑋=200 using the discontinuous Galerkin time domain method. A comparison of the DGTD solution for smoothly faceted particles with that obtained with a geometric optics model shows good agreement for the scattering angle curves of intensity and polarization. If a wavelength-scale surface roughness is introduced, diffuse scattering at rough interface results in smooth and featureless curves for all scattering matrix elements which is consistent with the laboratory measurements of real samples.
Keywords: tet_topic_scattering

Tunable optical parametric generator based on the pump spatial walk-off - Cavanna, Andrea; Just, Felix; Sharapova, Polina; Taheri, Michael; Leuchs, Gerd; Chekhova, Maria V. (Optics Letters)
Keywords: Atomic and Molecular Physics; and Optics

How planar optical waves can be made to climb dielectric steps - Hammer, Manfred; Hildebrandt, Andre; Förstner, Jens (Optics Letters)
We show how to optically connect guiding layers at different elevations in a 3-D integrated photonic circuit. Transfer of optical power carried by planar, semi-guided waves is possible without reflections or radiation losses, and over large vertical distances. This functionality is realized through simple step-like folds of high-contrast dielectric slab waveguides, in combination with oblique wave incidence, and fulfilling a resonance condition. Radiation losses vanish, and polarization conversion is suppressed for TE wave incidence beyond certain critical angles. This can be understood by fundamental arguments resting on a version of Snell’s law. The two 90° corners of a step act as identical partial reflectors in a Fabry–Perot-like resonator setup. By selecting the step height, i.e., the distance between the reflectors, one realizes resonant states with full transmission. Rigorous quasi-analytical simulations for typical silicon/silica parameters demonstrate the functioning. Combinations of several step junctions can lead to other types of optical on-chip connects, e.g., U-turn- or bridge-like configurations.
Keywords: tet_topic_waveguide

Subwavelength binary plasmonic solitons - Kou, Yao; Förstner, Jens (Optics Letters)
We study the formation of subwavelength solitons in binary metal-dielectric lattices. We show that the transverse modulation of the lattice constant breaks the fundamental plasmonic band and suppresses the discrete diffraction of surface plasmon waves. New types of plasmonic solitons are found, and their characteristics are analyzed. We also demonstrate the existence of photonic-plasmonic vector solitons and elucidate their propagation properties.
Keywords: tet_topic_polariton

Interaction of high-order solitons with external dispersive waves - Oreshnikov, I.; Driben, R.; Yulin, A. V. (Optics Letters)

Weak and strong interactions between dark solitons and dispersive waves - Oreshnikov, I.; Driben, R.; Yulin, A. V. (Optics Letters)

Interaction of high-order solitons with external dispersive waves - Oreshnikov, I.; Driben, R.; Yulin, A. V. (Optics Letters)

Weak and strong interactions between dark solitons and dispersive waves - Oreshnikov, I.; Driben, R.; Yulin, A. V. (Optics Letters)

Interaction of high-order solitons with external dispersive waves - Oreshnikov, I.; Driben, R.; Yulin, A. V. (Optics Letters)

Electro-optic tuning of split ring resonators embedded in a liquid crystal - Atorf, Bernhard; Mühlenbernd, Holger; Muldarisnur, Mulda; Zentgraf, Thomas; Kitzerow, Heinz-Siegfried (Optics Letters)

Measurement of group velocity dispersion in a solid-core photonic crystal fiber filled with a nematic liquid crystal - Wahle, Markus; Kitzerow, Heinz-Siegfried (Optics Letters)
Keywords: Atomic and Molecular Physics; and Optics

Bright squeezed-vacuum source with 11 spatial mode - Pérez, A. M.; Iskhakov, T. Sh.; Sharapova, Polina; Lemieux, S.; Tikhonova, O. V.; Chekhova, M. V.; Leuchs, G. (Optics Letters)
Keywords: Atomic and Molecular Physics; and Optics

Nonlinear dynamics of Airy-vortex 3D wave packets: emission of vortex light waves - Driben, Rodislav; Meier, Torsten (Optics Letters)
The dynamics of 3D Airy-vortex wave packets is studied under the action of strong self-focusing Kerr nonlinearity. Emissions of nonlinear 3D waves out of the main wave packets with the topological charges were demonstrated. Because of the conservation of the total angular momentum, charges of the emitted waves are equal to those carried by the parental light structure. The rapid collapse imposes a severe limitation on the propagation of multidimensional waves in Kerr media. However, the structure of the Airy beam carrier allows the coupling of light from the leading, most intense peak into neighboring peaks and consequently strongly postpones the collapse. The dependence of the critical input amplitude for the appearance of a fast collapse on the beam width is studied for wave packets with zero and nonzero topological charges. Wave packets carrying angular momentum are found to be much more resistant to the rapid collapse.

Coupled Airy breathers - Driben, R.; Konotop, V. V.; Meier, Torsten (Optics Letters)
The dynamics of two component-coupled vectorial Airy beams is investigated. In the linear propagation regime, a complete analytic solution describes the breather-like propagation of two components that feature nondiffracting self-accelerating Airy behavior. The superposition of two beams with different input properties opens the possibility of designing more complex nondiffracting propagation scenarios. In the strongly nonlinear regime, the dynamics remain qualitatively robust as is revealed by direct numerical simulations. Because of the Kerr effect, the two beams emit solitonic breathers whose coupling period is compatible with the remaining Airy-like beams. The results of this study are relevant for the description of photonic and plasmonic beams that propagate in coupled planar waveguides, as well as for birefrigent or multiwavelength beams.

Time-to-space conversion of ultrafast waveforms at 155 μm in a planar periodically poled lithium niobate waveguide - Shayovitz, Dror; Herrmann, Harald; Sohler, Wolfgang; Ricken, Raimund; Silberhorn, Christine; Marom, Dan M. (Optics Letters)
Keywords: Atomic and Molecular Physics; and Optics

Testing spectral filters as Gaussian quantum optical channels - Laiho, K.; Christ, A.; Cassemiro, K. N.; Silberhorn, Christine (Optics Letters)
Keywords: Atomic and Molecular Physics; and Optics

High-visibility, high-order lensless ghost imaging with thermal light - Chen, Xi-Hao; Agafonov, Ivan N.; Luo, Kai Hong; Liu, Qian; Xian, Rui; Chekhova, Maria V.; Wu, Ling-An (Optics Letters)

Lensless ghost imaging with true thermal light - Chen, Xi-Hao; Liu, Qian; Luo, Kai Hong; Wu, Ling-An (Optics Letters)

Shaping the spatiotemporal dynamics of the electron density in a hybrid metal-semiconductor nanostructure - Reichelt, Matthias; Meier, Torsten (Optics Letters)
A one-dimensional semiconductor nanostructure is locally excited through a metal aperture. It is shown that the electron density can be coherently localized at desired spatial and temporal positions by using nontrivially shaped laser pulses. To obtain the optimized laser field, Bloch equations for a tight-binding model system are solved together with a genetic pulse-shaping algorithm. Full three-dimensional finite-difference time-domain (FDTD) simulations of the Maxwell–Bloch equations confirm the predicted coherent spatiotemporal control.

Amplitude- and phase-resolved optical near fields of split-ring-resonator-based metamaterials - Zentgraf, Thomas; Dorfmüller, J.; Rockstuhl, C.; Etrich, C.; Vogelgesang, R.; Kern, K.; Pertsch, T.; Lederer, F.; Giessen, H. (Optics Letters)

Transition between different coherent light–matter interaction regimes analyzed by phase-resolved pulse propagation - zu Siederdissen, Tilman Höner; Nielsen, Nils C.; Kuhl, Jürgen; Schaarschmidt, Martin; Förstner, Jens; Knorr, Andreas; Khitrova, Galina; Gibbs, Hyatt M.; Koch, Stephan W.; Giessen, Harald (Optics Letters)
We present phase-resolved pulse propagation measurements that allow us to fully describe the transition between several light–matter interaction regimes. The complete range from linear excitation to the breakdown of the photonic bandgap on to self-induced transmission and self-phase modulation is studied on a high-quality multiple-quantum-well Bragg structure. An improved fast-scanning cross-correlation frequency-resolved optical gating setup is applied to retrieve the pulse phase with an excellent signal-tonoise ratio. Calculations using the semiconductor Maxwell–Bloch equations show qualitative agreement with the experimental findings.
Keywords: tet_topic_polariton; tet_topic_qw

Line narrowing and hole burning within the homogeneous linewidth: a new wave-mixing effect in two-level systems - Förstner, Jens; Knorr, A.; Lindberg, M.; Koch, S. W. (Optics Letters)
The interaction of strong low-area pulses with two-level systems shows absorption line narrowing and hole burning within the homogeneous linewidth as a result of nonlinear wave mixing. The wave mixing results from the two-level electronic saturation nonlinearity and occurs, depending on the sign of the pulse area, as a strong absorption enhancement or gain at the transition frequency of the two-level system for resonant excitation.
Keywords: tet_topic_polariton